2019
DOI: 10.21203/rs.2.9298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Obstructive Sleep Apnea in Mild Cognitive Impairment: A Systematic Review

Abstract: Background: Previous studies have shown that obstructive sleep apnea (OSA) is associated with a higher risk of cognitive impairment or dementia in the elderly, leading to deleterious health effects and decreasing quality of life. This systematic review aims to determine the prevalence of OSA in patients with mild cognitive impairment (MCI) and examine whether an association between OSA and MCI exists. Methods: We searched Medline, PubMed, Embase, Cochrane Central, Cochrane Database of Systematic Reviews, Psych… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
11
1
1
Order By: Relevance
“…Our data found that 67.4% of the elderly had high risk of developing OSA and 72.9% had MCI. A study in Chinese population found the OSA prevalence was 63.7% [21] and a study found that MCI prevalence among those with high risk of OSA was ranging from 11-70%, slightly lower from our study (72.9%) [21]. Our data suggests that age was not associated with cognitive impairment and this is different from a previous study [22].…”
Section: Discussioncontrasting
confidence: 99%
“…Our data found that 67.4% of the elderly had high risk of developing OSA and 72.9% had MCI. A study in Chinese population found the OSA prevalence was 63.7% [21] and a study found that MCI prevalence among those with high risk of OSA was ranging from 11-70%, slightly lower from our study (72.9%) [21]. Our data suggests that age was not associated with cognitive impairment and this is different from a previous study [22].…”
Section: Discussioncontrasting
confidence: 99%
“…2. There is a high prevalence of OSA in mental disorders ranges: anxiety disorder from 6.4% [19] to 57.1% [15], depressive disorder around 21.5% [40], psychotic disorders from 5.1% to 57.1% [19,63,64], bipolar disorder from 4.6% [75] to 15% [66], cognitive impairment from 11% to 71% [32]. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Beaudin et al in 2021 conducted a clinical cohort study in which they noted that CI was present in 47.9% of OSA patients and it increased with the severity of the symptoms [31]. In another systematic review, the prevalence of OSA in patients with mild cognitive impairment ranges from 11% to 71% [32]. The most affected areas in cognition are attention, episodic memory, working memory, executive functions, motor performance, and constructional abilities [27,28].…”
Section: Osa and Cognitive Impairmentmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a breathing disorder disease, which causes temporary cessation of airflow for 10 s while continuing ventilation during patients’ sleeping. 1 OSA is present in 4% of men and in 2% of women. Intermittent arterial oxygen desaturation, nocturnal arousal, and sleep disorders occur after a recurrent obstructive upper airway.…”
Section: Introductionmentioning
confidence: 99%